Isothermal and non-isothermal cold crystallization kinetics of polylactide/cellulose nanocrystal (PLA/CNC) nanocomposites - Alanalp, Mine Begum; Ozdemir, Burcu; Nofar, Mohammadreza; Durmus, Ali (Springer Science and Business Media LLC, 2022)
The effect of cellulose nanocrystal (CNC) content on the crystallization and melting behaviors of polylactide (PLA)/CNC nanocomposites prepared by solution mixing was investigated. Isothermal and non-isothermal cold crystallization kinetics of specimens were quantified using Ozawa, Avrami, and Liu-Mo methods. Overall and conversion dependent crystallization activation energy values were also determined through the Kissinger and Flynn-Wall-Ozawa equations. It was found that although CNC acted as a nucleating agent for cold crystallization of PLA under isothermal and non-isothermal conditions, it differently affected the crystal growth behavior. Kinetic calculations revealed that the increase in CNC amount decreased the non-isothermal cold crystallization rate of PLA possibly due to the reduced interaction among PLA molecules and formation of strong hydrogen bonding between the carboxyl groups of PLA and CNC surfaces. CNC addition also increased the overall cold crystallization activation energy whereas progress in crystallization yielded a significant reduce in the activation energy. This was because the relative crystallinity and temperature simultaneously increase during cold crystallization under non-isothermal conditions. Avrami analysis implied that CNC addition improved the crystallization rate of PLA possibly following athermal nucleation and two-dimensional discotic growth. [GRAPHICS] .
Keywords: Lactic-Acid; Thermal-Properties; Nanocomposites; Differantial scanning calorimeter (DSC); Fibers; Cellulose Nanocrystals; Crysallization; Blends; Enthalpy Relaxation; Behaviors; Biodegradable; Heating Rate; Pla; Polypropylene